2009
DOI: 10.1097/tp.0b013e3181b47f25
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 Significantly Prolongs the Survival of Fully Mismatched Cardiac Allografts in Mice

Abstract: A short-course administration of galectin-9 significantly prolonged the survival of fully allogeneic cardiac allografts, which was associated with the suppression of Th1 and Th17 immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 33 publications
5
48
1
1
Order By: Relevance
“…We now show that treatment with rGal-9 activated TIM-3 expression, diminished IR-triggered TLR4 activation and mitigated proinflammatory cytokine programs, ultimately leading to OLT cytoprotection. These beneficial effects are in agreement with the ability of Gal-9 to ameliorate diet-induced liver steatosis by modulating NKT cell function (31); prolong survival of fully allogeneic cardiac allografts by suppressing Th1/Th17 immune responses (32); or protect corneal allografts from destruction by allo-reactive T cells (33). …”
Section: Discussionsupporting
confidence: 71%
“…We now show that treatment with rGal-9 activated TIM-3 expression, diminished IR-triggered TLR4 activation and mitigated proinflammatory cytokine programs, ultimately leading to OLT cytoprotection. These beneficial effects are in agreement with the ability of Gal-9 to ameliorate diet-induced liver steatosis by modulating NKT cell function (31); prolong survival of fully allogeneic cardiac allografts by suppressing Th1/Th17 immune responses (32); or protect corneal allografts from destruction by allo-reactive T cells (33). …”
Section: Discussionsupporting
confidence: 71%
“…Systemic administration of recombinant galectin-9 (rgal-9) has been shown to improve allogeneic cardiac as well as skin grafts. 30,31 Increased allograft survival was consistent with deletion of CD4 ϩ Tim-3 ϩ Th1 cells. Because of these promising findings, it may be possible to develop the use of reagents, such as rgal-9, for use in the clinic.…”
mentioning
confidence: 81%
“…In a number of studies, Gal-9 has been administered to experimental autoimmune disease models and displayed therapeutic effects, including for experimental allergic encephalomyelitis, experimental autoimmune arthritis, and autoimmune diabetes (23,35,37). Our previous studies also revealed that Gal-9 prolongs the survival of allografts through inhibition of the activation of CD8 ϩ T cells and Th17 cells (8,32).…”
mentioning
confidence: 95%